Protein translation paradox: Implications in translational regulation of aging - Kim, Harper S.; Pickering, Andrew M. (Frontiers in Cell and Developmental Biology, 2023)
Protein translation is an essential cellular process playing key roles in growth and development. Protein translation declines over the course of age in multiple animal species, including nematodes, fruit flies, mice, rats, and even humans. In all these species, protein translation transiently peaks in early adulthood with a subsequent drop over the course of age. Conversely, lifelong reductions in protein translation have been found to extend lifespan and healthspan in multiple animal models. These findings raise the protein synthesis paradox: age-related declines in protein synthesis should be detrimental, but life-long reductions in protein translation paradoxically slow down aging and prolong lifespan. This article discusses the nature of this paradox and complies an extensive body of work demonstrating protein translation as a modulator of lifespan and healthspan.